Fibrosis Progression in HCV Carriers with Mild Hepatitis Who Possess the High‐Repetition Variant of the DRD4 Gene, a Genetic Marker for Binge‐Drinking and Risk‐Seeking Behavior: A Longitudinal Study. (8th January 2013) - Minisini, Rosalba; Boccato, Elisa; Favretto, Serena; Alaimo, Emanuele; Smirne, Carlo; Burlone, Michela E.; Bocchetta, Simone; Vandelli, Carmen; Colletta, Cosimo; Colletta, Alessandro; Pirisi, Mario
<x xml:space="preserve">Abstract</x> Background Alcohol is a major determinant of the outcome of chronic hepatitis C virus (HCV) infection, but self‐reported drinking habits lack reliability. We hypothesized that carriage of high‐repetition variants (HRV) of the variable number of tandem repeats (VNTR) in exon III of the dopamine receptor D4 gene, linked to binge‐drinking and risk‐seeking behavior, might be a proxy measure of alcohol consumption, and aimed to verify whether it may affect histologic outcome. Methods A cohort of HCV patients with normal or near‐normal aminotransferases (N = 128) underwent a liver biopsy as part of diagnostic work‐up. None admitted to exceed low‐risk alcohol consumption; most (90/128, 70%) described themselves as teetotalers. They received advice on abstaining from alcohol, but not antiviral treatment. After a median follow‐up period of 10 years, all underwent a second liver biopsy. HRV allele frequencies were compared with those of a group of healthy blood donors (N = 128) and related to liver histology. Results HRV allele frequencies were 0.19 in patients and 0.16 in controls (p = 0.182). In the subgroup of patients who admittedly had consumed alcohol, 20/38 (53%) carried HRV, in comparison with 27/90 patients (30%) who had denied to consume alcohol (p = 0.026 by Fisher's exact test). Carriage of HRV was associated with higher histologic grade (p = 0.002) and stage (p = 0.009) at the final biopsy. At multivariate analysis, among a set of variables also including viral genotype, viral load, body mass index, gender, and history of alcohol consumption, only age (OR = 1.06, 95% CI 1.02 to 1.11) and HRV (OR = 3.13, 95% CI 1.28 to 7.68) were independent predictors of significant fibrosis at the end of follow‐up. Conclusions The link between HRV carriage and histologic outcome in a subgroup of HCV patients at low risk of progression underlines the need for intense scrutiny of alcohol habits in hepatitis C.